Gastrointestinal microbiome, what is behind faecal microbiota transplantation?. (July 2021) - Thomson, P.; Núñez, P.; Quera, R.; Bay, C.
Abstract: The intestinal microbiota is made up of billions of microorganisms that coexist in an organised ecosystem, where strict and facultative anaerobic bacteria predominate. The alteration or imbalance of these microorganisms, known as dysbiosis, can be associated with both gastrointestinal and extraintestinal diseases. Based on a review of the literature, the intestinal microbiota is described in its state of health, the changes associated with some gastrointestinal diseases and the potential role that faecal microbiota transplantation has in the reestablishment of an altered ecosystem. Undoubtedly, the information revealed makes us reflect on the indication of faecal microbiota transplantation in various pathologies of intestinal origin. However, to ensure the efficacy and safety of this therapy, more studies are needed to obtain more evidence. Highlights: The intestinal microbiota is a complex system which coexists up of billions of microorganisms. Dysbiosis is an alteration or imbalance of the microbiome and it can be seen in some gastrointestinal illness. The faecal microbiota transplantation can restore this altered ecosystem.